2017 IEEE 30th International Conference on Micro Electro Mechanical Systems (MEMS) 2017
DOI: 10.1109/memsys.2017.7863399
|View full text |Cite
|
Sign up to set email alerts
|

MEMS tunable silicon photonic grating coupler for post-assembly optimization of fiber-to-chip coupling

Abstract: We experimentally demonstrate the first MEMS tunable photonic fiber-to-waveguide grating coupler, and apply it to electrostatically optimize the light coupling between an optical fiber and an on-chip silicon photonic waveguide. Efficient and stable fiber-to-chip coupling is vital for combining the high optical quality of silica fibers with the integration density of silicon photonics. Our device has the potential to lower assembly cost and extend device lifetime, by enabling electrical post-assembly adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…2d 1, SEM in Fig. 11b), Errando-Herranz et al [98] demonstrated a spatial shift in the coupling to an optical fiber. This approach was adapted by Yu et al (Fig.…”
Section: Grating Couplersmentioning
confidence: 86%
See 1 more Smart Citation
“…2d 1, SEM in Fig. 11b), Errando-Herranz et al [98] demonstrated a spatial shift in the coupling to an optical fiber. This approach was adapted by Yu et al (Fig.…”
Section: Grating Couplersmentioning
confidence: 86%
“…Mode matching is highly dependent on the devices to be interfaced. So far, the only investigated application has been in fiber-to-chip alignment, with demonstrated 6 µm maximum tuning with 6 V along one direction [98], at the expense of varying transmission efficiency. Future work in this direction can benefit from additional tuning in the perpendicular direction, by e.g., tilting the device sideways in a similar way to MEMS micromirrors [19].…”
Section: Grating Couplersmentioning
confidence: 99%
“…20 This changes the diffraction pattern in the grating, which changes the light distribution in the grating and allows tuning of the alignment optimum in one direction. A schematic of the tunable grating coupler is shown in 5(a).…”
Section: Tunable Grating Couplermentioning
confidence: 99%
“…The sensitivity of the grating structure could be analyzed and evaluated using the change in coupled power as a function of the effective refractive index and was found to be 0.928 × 10 −6 RIU. The SOI optical grating structure along with the micro fluidic channel on top could be effectively used as an absorbance-based lab-on-a-chip biosensor.Photonics 2019, 6, 71 2 of 9 changes in physical parameters such as temperature, pressure, and magnetic field [17][18][19][20][21]. The Bragg wavelength for optical sensing applications is given by Equation (1) [22]:…”
mentioning
confidence: 99%
“…Photonics 2019, 6, 71 2 of 9 changes in physical parameters such as temperature, pressure, and magnetic field [17][18][19][20][21]. The Bragg wavelength for optical sensing applications is given by Equation (1) [22]:…”
mentioning
confidence: 99%